1989
DOI: 10.1084/jem.169.4.1199
|View full text |Cite
|
Sign up to set email alerts
|

Site-restricted persistent cytomegalovirus infection after selective long-term depletion of CD4+ T lymphocytes.

Abstract: We have established a murine model system for exploring the ability of a CD4 subset-deficient host to cope with cytomegalovirus infection, and reported three findings. First, an antiviral response of the CD8 subset of T lymphocytes could be not only initiated but also maintained for a long period of time despite a continued absence of the CD4 subset, whereas the production of antiviral antibody proved strictly dependent upon help provided by the CD4 subset. Second, no function in the defense against infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
339
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(357 citation statements)
references
References 45 publications
(38 reference statements)
15
339
2
Order By: Relevance
“…Doses of 10 6 and 10 5 M38-specific CD8 + T cells provided antiviral protection in peripheral tissues of immunocompromised mice, whereas 10 4 M38-specific CD8 + T cells did not confer protection in any of the organs tested except in the spleen. Of note, none of the transferred doses of M38-specific CD8 + T cells could mediate protection in the salivary glands, further confirming previous findings of the crucial role of CD4 + T cells in mucosal immunity toward CMV in this particular tissue [15,16]. Next, to test whether the co-transfer of M25-specific CD4 + T cells with M38-specific CD8 + T cells would synergize in antiviral immunity, graded numbers of in vivo activated, FACS sorted M25-or M38-specific cells were transferred in combination or alone into sublethally irradiated mice, followed by MCMV infection (Fig.…”
supporting
confidence: 75%
“…Doses of 10 6 and 10 5 M38-specific CD8 + T cells provided antiviral protection in peripheral tissues of immunocompromised mice, whereas 10 4 M38-specific CD8 + T cells did not confer protection in any of the organs tested except in the spleen. Of note, none of the transferred doses of M38-specific CD8 + T cells could mediate protection in the salivary glands, further confirming previous findings of the crucial role of CD4 + T cells in mucosal immunity toward CMV in this particular tissue [15,16]. Next, to test whether the co-transfer of M25-specific CD4 + T cells with M38-specific CD8 + T cells would synergize in antiviral immunity, graded numbers of in vivo activated, FACS sorted M25-or M38-specific cells were transferred in combination or alone into sublethally irradiated mice, followed by MCMV infection (Fig.…”
supporting
confidence: 75%
“…1). The responses specific for peptides m18 872-886 , M25 409 -423 , m139 560 -574 , m141 [181][182][183][184][185][186][187][188][189][190][191][192][193][194][195] , and m142 24 -38 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . The sum of these individual responses represented ϳ1.5% of the total splenic CD4 T cells following MCMV infection.…”
Section: Identification Of Mcmv-specific I-a B -Restricted Cd4 T Cellmentioning
confidence: 99%
“…Adoptive transfer of virus-specific CD8 T cells protects against CMVmediated disease in immunocompromised humans, and their maintenance requires human CMV-specific CD4 T cells (6). Similarly, the transfer of virus-specific CD8 T cells protects immunocompromised mice from disease (7), but acute MCMV infection is effectively controlled when CD8 T cells are absent in immunocompetent mice (3,8), highlighting a role for CD4 T cells in healthy mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Primary CMV infection of neonates and infants usually results in continuous or frequent viral shedding into the urine and saliva for up to several years (3,4). In contrast, limited studies have indicated that adults with primary CMV infection stop continual viral shedding by 9 -12 mo after acquisition, and have only infrequent recurrences of shedding thereafter (8,9).…”
mentioning
confidence: 99%